# Factorize by Grouping The Terms

Factorize by grouping the terms (two or more) means that we need to group the terms which have common factors before factoring.

Method to factorize by grouping the terms:

(i) From the groups of the given expression a common factor can be taken out from each group.

(ii) Factorize each group

(iii) Now take out the factor common to group formed.

Now we will learn how to factorize by grouping two or more terms.

Solved examples to factorize by grouping the terms:

1. Factorize grouping the following expressions:

(i) 18a3b3 - 27a2b3 + 36a3b2

Solution:

18a3b3 - 27a2b3 + 36a3b2

= 9a2b2(2ab – 3b + 4a)

(ii) 12x2y3 - 21x3y2

Solution:

12x2y3 - 21x3y2

= 3x2y2(4y - 7x)

(iii) y3 - y2 + y - 1

Solution:

y3 - y2 + y - 1

= y2(y - 1) + 1(y - 1)

= (y - 1) (y2 + 1)

(iv) axy + bcxy – az – bcz

Solution:

axy + bcxy – az – bcz

= xy(a + bc) – z(a + bc)

= (a + bc) (xy – z)

(v) x2 - 3x – xy + 3y

Solution:

x2 - 3x – xy + 3y

= x(x - 3) - y(x - 3)

= (x - 3) (x – y)

2. How to factorize by grouping the following expressions?

(i) 2x4 – x3 + 4x - 2

Solution:

2x4 – x3 + 4x - 2

= x3(2x – 1) + 2(2x - 1)

= (2x – 1) (x3 + 2)

(ii) pr + qr - ps - qs

Solution:

pr + qr - ps - qs

= r(p + q) - s(p + q)

= (p + q) (r - s)

(iii) mx - my - nx - ny

Solution:

mx - my - nx - ny

= m(x - y) - n(x - y)

= (x - y) (m - n)

3. How to factorize by grouping the algebraic expressions?

(i) a2c2 + acd + abc + bd

Solution:

a2c2 + acd + abc + bd

= ac(ac + d) + b(ac + d)

= (ac + d) (ac + b)

(ii) 5a + ab + 5b + b2

Solution:

5a + ab + 5b + b2

= a(5 + b) + b(5 + b)

= (5 + b) (a + b)

(iii) ab - by - ay + y2

Solution:

ab - by - ay + y2

= b(a - y) - y(a - y)

= (a - y) (b - y)

4. Factorize the expressions:

(i) x4 + x3 + 2x + 2

Solution:

x4 + x3 + 2x + 2

= x3(x + 1) + 2 (x + 1)

= (x + 1) (x3 + 2)

(ii) f2x2 + g2x2 – ag2 – af2

Solution:

f2x2 + g2x2 – ag2 – af2

= x2(f2 + g2) – a (g2 + f2)

= x2(f2 + g2) – a(f2 + g2)

= (f2 + g2)(x2 – a)

5. Factorize by grouping the terms (a2 + 3a)2 - 2(a2 + 3a) – b(a2 + 3a) + 2b

Solution:

(a2 + 3a)2 - 2(a2 + 3a) – b(a2 + 3a) + 2b

= [(a2 + 3a)2 - 2(a2 + 3a)] – [b(a2 + 3a) - 2b]

= (a2 + 3a) (a2 + 3a - 2) – b(a2 + 3a - 2)

= (a2 + 3a - 2) (a2 + 3a - b)

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Lines of Symmetry | Symmetry of Geometrical Figures | List of Examples

Aug 10, 24 04:59 PM

Learn about lines of symmetry in different geometrical shapes. It is not necessary that all the figures possess a line or lines of symmetry in different figures.

2. ### Symmetrical Shapes | One, Two, Three, Four & Many-line Symmetry

Aug 10, 24 02:25 AM

Symmetrical shapes are discussed here in this topic. Any object or shape which can be cut in two equal halves in such a way that both the parts are exactly the same is called symmetrical. The line whi…

Aug 10, 24 01:59 AM

In 6th grade math practice you will get all types of examples on different topics along with the step-by-step explanation of the solutions.

4. ### 6th Grade Algebra Worksheet | Pre-Algebra worksheets with Free Answers

Aug 10, 24 01:57 AM

In 6th Grade Algebra Worksheet you will get different types of questions on basic concept of algebra, questions on number pattern, dot pattern, number sequence pattern, pattern from matchsticks, conce…